Analisis Faktor-Faktor Hambatan Membaca Permulaan Siswa Kelas 1 SD GMIT Oesapa - bethan, vebri; Djuli, Labu; Koro, Maxsel (Journal of Character and ELementary Education, 2025)
This research using qualitative research aims to determine the types of initial reading barriers in language sounds, factors that influence initial reading barriers, and how to overcome initial reading barriers in grade 1 students at GMIT Oesapa Elementary School. This type of research is a case study. The subjects of this research were 19 students. Data collection was carried out using observation techniques, interviews and documentation studies. The collected data was analyzed using qualitative descriptive analysis. This research obtained results that there were 19 students and 3 students experienced obstacles in beginning reading. This research process began with observations with the class I teacher, then carried out tests directly on students, then after the aspects of difficulty were known, students were observed who experienced obstacles in beginning reading. Barriers to beginning reading among grade I students at GMIT Oesapa Elementary School range from difficulty in identifying letters, reversing letters, difficulty in recognizing the meaning of words, lack of understanding of the content of the reading, halting spelling, and difficulty in understanding and listening to the text being read.